Tumor-Derived CXCL1 Promotes Lung Cancer Growth via Recruitment of Tumor-Associated Neutrophils - Ming Yuan; Ha Zhu; Junfang Xu; Yuanyuan Zheng; Xuetao Cao; Qiuyan Liu (Journal of Immunology Research)
Neutrophils have a traditional role in inflammatory process and act as the first line of defense against infections. Although their contribution to tumorigenesis and progression is still controversial, accumulating evidence recently has demonstrated that tumor-associated neutrophils (TANs) play a key role in multiple aspects of cancer biology. Here, we detected that chemokine CXCL1 was dramatically elevated in serum from 3LL tumor-bearing mice. In vitro, 3LL cells constitutively expressed and secreted higher level of CXCL1. Furthermore, knocking down CXCL1 expression in 3LL cells significantly hindered tumor growth by inhibiting recruitment of neutrophils from peripheral blood into tumor tissues. Additionally, tumor-infiltrated neutrophils expressed higher levels of MPO and Fas/FasL, which may be involved in TAN-mediated inhibition of CD4+ and CD8+ T cells. These results demonstrate that tumor-derived CXCL1 contributes to TANs infiltration in lung cancer which promotes tumor growth.